Meme and cyber sexism: Habitus and symbolic violence of patriarchy on the Internet - Moh. Faiz Maulana (SIMULACRA: JURNAL SOSIOLOGI, 2021)
This study examines the various sexist practices on the Internet called cyber sexism. The Internet seems to become a new world for patriarchal domination. The amount of content, comments, and memes circulating on the Internet and social media, such as Instagram, Facebook, Twitter, and WhatsApp harassing women, is proof of the patriarchal power on the Internet. This study used a qualitative method with a feminist perspective, collecting memes through Instagram, Facebook, Twitter, and WhatsApp. The memes were then reviewed and interpreted to find their meaning. Using Pierre Bourdieu’s habitus theory and symbolic violence, memes were analyzed to find the factors that cause sexism against women and the logical link between sexist practices in the real world and cyber sexism on the Internet. Results indicate that people’s habitus about patriarchy has become a mental structure of society that influences stereotyped behavior and gender bias and plays an important role in sexism on the Internet. The Internet, as an arena, has become the initial capital for men to dominate. Naming and mentioning women in various memes are the forms of symbolic violence against them that form new sexist habitus on the Internet.